Matrix effect in a view of lc-ms/ms: an overview - DHARMENDRA PATEL (International Journal of Pharma and Bio Sciences, 2011)
Despite their enormous utility and diffusion, atmospheric pressure ionization mass spectrometry techniques are subjected to relevant drawbacks called matrix effects (ME). These effects could be summarized in matrix-dependent signal suppression or enhancement that could lead to erroneous quantitative results. The most important method parameters as well as linearity, precision, and accuracy could be modified due to interfering compounds present in the matrix. No validation methods could be accepted without a thorough evaluation of ME and possible strategies to minimize or to correct their influence should be addressed. Matrix effects result from co-eluting residual matrix components affecting the ionization efficiency of target analytes and can lead to erroneous results. Matrix effects, i.e. ion suppression or ion enhancement, are well known phenomena in liquid chromatography-mass spectrometry (LC-MS). They can be caused by compounds of various origins. Since matrix effects may exert a negative effect on important method performance parameters, they have to be tested for and evaluated during method development/validation. This can either be done by the method of postcolumn infusion or by comparison of signals from neat standards and blank sample extracts spiked with analyte. Wherever possible, matrix effects should be reduced or eliminated by the optimization of chromatographic conditions, improving sample clean-up and/or by changing the type of ionization employed. In the present article, we have concentrated on detailed description of matrix effects in a view of LC-MS/MS.